Pertanggungjawaban Perdata Pengguna Media Sosial atas Pencemaran Nama Baik: Analisis KUHPerdata & UU ITE - Tarindra Rahmadani Azhara (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Defamation cases through social media platforms are increasing along with freedom of expression in the digital cyberspace. Many cases have succeeded in recovering immaterial losses for victims, but settlement through civil channels is still rarely used compared to criminal approaches. his study aims to analyze the basis for civil liability of social media users for defamation based on Article 1365 of the Civil Code and its relationship to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) as amended. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. The results show that defamation through social media fulfills the elements of an unlawful act as referred to in Article 1365 of the Civil Code. The ITE Law functions as a lex specialis that regulates electronic means and strengthens digital evidence. However, the main obstacles lie in proving malicious intent, the identity of anonymous perpetrators, and the assessment of immaterial losses. This study concludes that the synergy between the Civil Code and the ITE Law needs to be optimized through digital evidence guidelines and cyber dispute resolution mechanisms that are more adaptive to technological developments.